2010
DOI: 10.1248/bpb.33.301
|View full text |Cite
|
Sign up to set email alerts
|

Timolol Activates the Enzyme Activities of Human Carbonic Anhydrase I and II

Abstract: Therapy for glaucoma is generally individualized for each glaucoma patient, with several factors, including intraocular pressure (IOP) and the degree of optic nerve damage, given consideration. In the treatment of glaucoma, several types of agents such as beta-blockers, prostaglandin analogues and carbonic anhydrase (CA) inhibitors are clinically used at present in pharmacotherapy.1-2) Beta-blockers or prostaglandin F2-alpha analogues have been shown to be effective ocular hypotensive agents when used alone in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…Interestingly, pharmacological agents born for other medical applications ( Figure 4 ) showed also to possess more or less relevant CA-activating effects, among which psychoactive compounds of the amphetamine and methamphetamine family 54 , the selective serotonin reuptake inhibitors fluoxetine, sertraline and citalopram 55 , the phosphodiesterase IV inhibitor sildenafil 56 , and the β-blocker amino alcohol derivative timolol 57 . Timolol was taken as lead compound in the present study to design a new series of uncommon CAAs, which do not bear imidazole like scaffolds, intesively explored in the field.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, pharmacological agents born for other medical applications ( Figure 4 ) showed also to possess more or less relevant CA-activating effects, among which psychoactive compounds of the amphetamine and methamphetamine family 54 , the selective serotonin reuptake inhibitors fluoxetine, sertraline and citalopram 55 , the phosphodiesterase IV inhibitor sildenafil 56 , and the β-blocker amino alcohol derivative timolol 57 . Timolol was taken as lead compound in the present study to design a new series of uncommon CAAs, which do not bear imidazole like scaffolds, intesively explored in the field.…”
Section: Resultsmentioning
confidence: 99%
“…The molecule of histamine has been extensively modified (Figure 3), including substituents on the imidazole C atoms (A) 41,42 , replacing the imidazole ring with other heterocycles, such as 2,4,6-trisubstituted pyridinium (B), 1,3,4-thiadiazole (C) or a combination of these two ring systems (D) 43,44 and functionalising the NH 2 group, as in carboxamides/ureas/thioureas (E) 45 , sulphonamides (F) 46 , arylsulfonylureas (G) 47 , bis-histamine (H) 48,49 , oligopeptides 49,50 , or imidazole/imidazoline derivatives of the alkaloyd spinaceamine 51,52 and drug clonidine 53 (Figure 3) were reported to possess improved CA activatory profile when potency and isoform selectivity are concerned. Interestingly, pharmacological agents born for other medical applications (Figure 4) showed also to possess more or less relevant CA-activating effects, among which psychoactive compounds of the amphetamine and methamphetamine family 54 , the selective serotonin reuptake inhibitors fluoxetine, sertraline and citalopram 55 , the phosphodiesterase IV inhibitor sildenafil 56 , and the b-blocker amino alcohol derivative timolol 57 . Timolol was taken as lead compound in the present study to design a new series of uncommon CAAs, which do not bear imidazole like scaffolds, intesively explored in the field.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Na + /K + -ATPase, Mg 2+ -ATPase, and prostaglandin biosynthesis (Watanabe and Chiou 1983); what is more, it has been recently demonstrated that timolol activates the enzyme activities of human CA-II (Sugimoto et al 2010).…”
Section: Mechanism Of Actionmentioning
confidence: 95%
“…The structure of the timolol-hCA-I or -hCA-II complex8) A: The structure of the timolol-hCA-I complex superimposed onto that of the timolol-hCA-II complex. The rounded ribbon model structures of hCA-I and hCA-II are shown in white and magenta, respectively, and the zinc ions located at the active sites are shown as a green space fill model.…”
mentioning
confidence: 99%